VD_FINDINFO Jug / 2015 / 268 vom 9. April 2015 - VD Tribunal cantonal (2015)
DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC, ENSEIGNANT, RÉPRIMANDE, PROPORTIONNALITÉ | 14 LPers-VD, 16 al. 3 LPers-VD, 50 LPers-VD, 59 LPers-VD, 135 RLPers-VD